Portable Filter-Free Lens-Free Incoherent Digital Holography System - Tatsuki Tahara (Photonics)
A portable incoherent digital holography system without a polarization filter or a refractive lens was developed. Phase-shifted self-interference incoherent holograms of light diffracted from an object were generated without attenuation due to a polarization filter using two polarization-sensitive phase-only spatial light modulators (TPP-SLMs). The number of optical elements in filter-free lens-free incoherent digital holography was reduced to make the system compact and portable. Experiments were conducted using the developed digital holography system set on a tripod stand and objects illuminated by a light-emitting diode.